2021
DOI: 10.1371/journal.pone.0260321
|View full text |Cite
|
Sign up to set email alerts
|

The coronavirus disease 2019 (COVID-19) vaccination psychological antecedent assessment using the Arabic 5c validated tool: An online survey in 13 Arab countries

Abstract: Background Following the emergency approval of the coronavirus disease 2019 (COVID-19) vaccines, research into its vaccination hesitancy saw a substantial increase. However, the psychological behaviors associated with this hesitancy are still not completely understood. This study assessed the psychological antecedents associated with COVID-19 vaccination in the Arab population. Methodology The validated Arabic version of the 5C questionnaire was distributed online across various social media platforms in Ara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 50 publications
(56 reference statements)
1
40
2
Order By: Relevance
“…List of papers rejected and causes of rejection are provided as Supplementary Table S2 . References [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] are cited in Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…List of papers rejected and causes of rejection are provided as Supplementary Table S2 . References [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] are cited in Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
“…Although some of the vaccines were approved for emergency use by the FDA in the USA and the respective health departments of other countries across the world, the efficacy and effectiveness should be periodically assessed due to the ongoing antigenic drift. It is worth noting that while vaccinations are still being administered worldwide, the vaccinated population (received at least one dose of vaccine) represents around three-fifth of the entire population [ 59 ], with safety and effectiveness representing the main concern and points of hesitation for many people [ 25 ]. Another main concern affecting vaccination coverage is COVID-19 vaccine inequity; vaccine supply will have a long-term and severe impact on socioeconomic recovery in low-and lower-middle-income countries (LMIC) unless immediate action is taken to increase supply and provide equal access for all countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides empirical evidence for the safety and immunogenicity of COVID-19 vaccines, and this is crucial as demonstrating the safety and benefits of COVID-19 vaccines is critical to enhance public trust in COVID-19 vaccination, particularly in countries with high rates of vaccine hesitancy. 24 , 50 Moreover, results from this analysis will provide information about the number of days required for the development of anti-SARS-CoV-2 antibodies developed from the sequential immunization strategy. Information on the duration of the development of the commonly reported vaccine adverse effects across various vaccine technology platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on vaccine hesitancy found that the refusal or delaying the vaccination was affected by the population’s trust in the safety and efficacy of vaccines. 24 …”
Section: Introductionmentioning
confidence: 99%